2015
DOI: 10.1111/flan.12122
|View full text |Cite
|
Sign up to set email alerts
|

Students With Learning Disabilities in the Foreign Language Learning Environment and the Practice of Exemption

Abstract: This examination of the literature on foreign, or second, language learning by native English-speaking students with disabilities addresses the benefits of language learning, the practices and policies of language exemption, the perceptions of students and educators regarding those practices, and available resources for supporting students with special needs. It aims to question the policy of granting foreign language exemptions while additionally providing insights for educators into the development of inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 69 publications
1
48
0
2
Order By: Relevance
“…Even in cases where special needs students did not respond verbally to a question (interpersonal communication) during the assessment, they were able to indicate that they understood the question (interpretive communication) by pointing to a red color card in response to the question, "Can you show me rouge [red]?" These findings challenge a belief rooted in deficit thinking (Wight, 2015) that special needs students should be exempted from foreign language study. Although much more research is needed, this study shows that foreign language learning is accessible to special needs students when they are provided with sufficient opportunities to engage in L2 exchanges.…”
Section: Assessment Scoresmentioning
confidence: 50%
“…Even in cases where special needs students did not respond verbally to a question (interpersonal communication) during the assessment, they were able to indicate that they understood the question (interpretive communication) by pointing to a red color card in response to the question, "Can you show me rouge [red]?" These findings challenge a belief rooted in deficit thinking (Wight, 2015) that special needs students should be exempted from foreign language study. Although much more research is needed, this study shows that foreign language learning is accessible to special needs students when they are provided with sufficient opportunities to engage in L2 exchanges.…”
Section: Assessment Scoresmentioning
confidence: 50%
“…For example, when conducting a random search of the accommodations policies of 50 different public and private U.S. colleges and universities, the author found that even though there were some minor differences in their policies, each institution required that a student be classified as disabled—in most cases, as LD—to apply for course substitutions and waivers of the FL requirement. Similarly, Wight () found that, for secondary‐level students, most school districts and private schools set their own policies, formal or informal, for course substitutions and waivers, although a state might adopt specific policies. In their examination of college and university policies regarding the FL requirement, Lys, May, and Ravid () found that most institutions did not assist students classified as LD in choosing the most appropriate FL courses, nor did they focus on providing support for FL study.…”
Section: Beliefs Policies and Practicesmentioning
confidence: 99%
“…However, these assumptions and recommendations—that there is a “special” relationship between LDs and FL learning and a specific “disability” that justifies classification as an LD and requires special accommodations—are not supported by empirical evidence. Rather, they are supported by case studies of individual learners (Abrams, ), case studies of modified classes and special programs (Leons, Herbert, & Gobbo, ), personal anecdotes (Simon, ), educators who have made decisions about foreign language accommodations (Scott & Banerjee, ), and literature reviews of course substitution and waiver policies (Wight, ).…”
Section: Beliefs Policies and Practicesmentioning
confidence: 99%
“…For instance, Wight (2015) states that students with disabilities are indeed more likely to be excluded from MFL lessons than other students in many Anglophonic countries, including Scotland. Wight (2015) notes that the idea persists that language learning is based on 'ability' or perceived intelligence and that current assessments of proficiency contribute to the perpetuation of the notion that some students should be excluded from MFL without ever having a chance to participate. This finding echoes those of Stalker and Moscardini (2012), who argue that attitudinal barriers are the major factor is precluding learners from full curricular access, in direct contrast to the European Commission's forcible assertion that if we deny any student the experience of MFL learning because of our low expectations, then we are effectively denying them an aspect of European citizenship.…”
Section: Inclusion and Entitlement In The Scottish Contextmentioning
confidence: 99%
“…This article focuses on students in Scotland with additional support needs (ASN) for whom, by virtue of their age, MFL education is mandatory, but who are frequently not receiving their curricular entitlement. It responds to previous authors' demands to understand more clearly the extent of equality of access to MFL education (Stevens and Marsh, 2005;Wight, 2015). The review considers the policy landscape around MFL provision and the apparent mismatch between aspiration and practice.…”
Section: Introductionmentioning
confidence: 98%